ҚАРАҚАЛПАҚСТАНДА БИЛИНГВИЗМ МӘСЕЛЕСИ - Шынназарова, С.Ж.; Мамбетова, Г.Ж. (FAN va JAMIYAT, 2024)
The article reveals the concept of «bilingualism» as a social phenomenon. The relevance of this problem in modern society is emphasized. The views of bilingualism researchers, as well as modern approaches to this problem, are considered.